(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The present study was conducted to examine the effect of 100 aggressive and 100 non-aggressive student selected on the basis of 25 percent higher and 25 present lowest scoring on Manifest Aggression Scale social emotional and total adjustment including self-estimate. Adjustment was Bell’s adjustment (Hindi Adaptation) and self esticate was measured by health adjustment, home adjustment, social adjustment, emotional adjustment, total adjustment and self-esteem. On the basis of the finding of the study it may be concluded that aggressive and non-aggressive groups of schools students differ significant in adjustment and self-esteem and aggressive groups of school students are poor in home, health, social, emotional including overall adjustment as compared to non-aggressive groups of students. Aggressive groups of students are generally lower in self-esteem than non-aggressive groups of student.